1994
DOI: 10.1093/jmedent/31.3.435
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride-Rich Lipophorin in Aedes aegypti (Diptera: Culicidae)

Abstract: A lipoprotein was isolated from Aedes aegypti (L.) larvae. This lipoprotein resembled the typical lipoprotein responsible for lipid transport in insect hemolymph, also called lipophorin. The mosquito lipophorin had a hydrated density of 1.113 g/ml and contained 49% lipid and 3.2% carbohydrate. In contrast to all other insect species studied thus far, the major lipid component of the mosquito lipophorin was triacylglycerol. The native lipophorin had an apparent molecular weight of 480 kd and contained two subun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 0 publications
3
27
0
Order By: Relevance
“…The amino acid composition of B. germanica HDLp shows considerable similarity to lipophorins from other species, such as, D. punctata (King and Tobe, 1992), Philosamia cynthia (Chino et al, 1977), Aedes aegypti (Ford and Van Heusden, 1994), and others. Indeed, an earlier principal component analysis of amino acid compositions concluded that lipophorins from various insects formed a distinct group, separate from vitellogenins (Kunkel and Nordin, 1985).…”
Section: Composition Of Lipophorinmentioning
confidence: 87%
“…The amino acid composition of B. germanica HDLp shows considerable similarity to lipophorins from other species, such as, D. punctata (King and Tobe, 1992), Philosamia cynthia (Chino et al, 1977), Aedes aegypti (Ford and Van Heusden, 1994), and others. Indeed, an earlier principal component analysis of amino acid compositions concluded that lipophorins from various insects formed a distinct group, separate from vitellogenins (Kunkel and Nordin, 1985).…”
Section: Composition Of Lipophorinmentioning
confidence: 87%
“…gambiae lipophorin is similar to M. sexta (Pattnaik et al, 1979), Rhodnius prolixus (Gondim et al, 1989), Ae. aegypti (Ford and Van Heusden, 1994) and other insects (Chino, 1985). An.…”
Section: Discussionmentioning
confidence: 99%
“…In Ae. aegypti, triacylglycerol is the most abundant (32% of the total) lipid (Ford and Van Heusden, 1994). On the other hand, hydrocarbons are the predominant lipid class in Periplaneta americana (Chino et al, 1981) and Leptinotarsa decemlineata (Katagiri et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…In adult M. sexta, FFA account for 5.2% of the lipids of HDLp (DAG 25%, PL 14%) and for 3.5% of the lipids of LDLp (Ryan et al, 1986b) (DAG 46.9%, PL 7%). In Aedes aegypti, FFA account for 7-14% of the lipids of HDLp (Ford and Van Heusden, 1994;Pennington et al, 1996).…”
Section: Lipoprotein-mediated Lipid Transportmentioning
confidence: 99%
“…It is not known, whether the oocytes take up TAG, or whether TAG is first broken down to FFA. The high content of FFA (7-14%) of the mosquito HDLp (Ford and Van Heusden, 1994;Pennington et al, 1996) might be important for supplying lipids to the oocytes.…”
Section: Receptor-mediated Lipid Deliverymentioning
confidence: 99%